Bioenergetics of Mammalian Sperm Capacitation. (25th March 2014) - Ferramosca, Alessandra; Zara, Vincenzo
Abstract : After ejaculation, the mammalian male gamete must undergo the capacitation process, which is a prerequisite for egg fertilization. The bioenergetics of sperm capacitation is poorly understood despite its fundamental role in sustaining the biochemical and molecular events occurring during gamete activation. Glycolysis and mitochondrial oxidative phosphorylation (OXPHOS) are the two major metabolic pathways producing ATP which is the primary source of energy for spermatozoa. Since recent data suggest that spermatozoa have the ability to use different metabolic substrates, the main aim of this work is to present a broad overview of the current knowledge on the energy-producing metabolic pathways operating inside sperm mitochondria during capacitation in different mammalian species. Metabolism of glucose and of other energetic substrates, such as pyruvate, lactate, and citrate, is critically analyzed. Such knowledge, besides its obvious importance for basic science, could eventually translate into the development of novel strategies for treatment of male infertility, artificial reproduction, and sperm selection methods.